Penyuluhan Hipertensi Dengan Terapi Komplementer Jus Tomat Di Wilayah Dusun 4 Desa Sumbersari Kecamatan Kabawetan Tahun 2025 - Ambarwati, Meli; Amelia, Reli; Elpianti, Yetri; Elpia, Zetri; Rustandi, Handi; Sari, Fikitri Marya; Epriana S, Meri; Rohani, Tuti; Azissah, Danur (Jurnal Dehasen Untuk Negeri, 2025)
Hypertension is one of the non-communicable diseases that can cause serious complications if not treated properly. Giving tomato juice as an alternative to non-pharmacological treatment can help lower blood pressure. With the aim of determining the effect of hypertension counseling by administering tomato juice on lowering blood pressure in hypertensive patients. Hypertension counseling through the lecture method to the productive age community in Sumber Sari village. Hypertension counseling with tomato juice can help lower blood pressure in hypertensive patients. Therefore, giving tomato juice can be one of the alternative non-pharmacological treatments to help manage hypertension.